Evidence of large sturgeons in the Paleocene of North America. (January 2023) - Brownstein, Chase Doran
Abstract: Ray-finned fishes comprise nearly half of extant vertebrate species and include several ancient lineages with fossil records that stretch over 200 Myr in time. One of these old clades, the sturgeons and paddlefishes, is distributed across the Northern Hemisphere and includes some of the largest known freshwater fishes. Yet, the fossil record of this lineage (Acipenseriformes) is poor compared to similarly ancient ray-finned fish clades. Here, I describe sturgeon fossils from two geological units in North America < 10 Myr younger than the Cretaceous-Paleogene boundary. Both come from individuals of ~1.5 m in length. These Paleogene forms establish the long history of large body size in Acipenseriforms and reveal sturgeons were some of the largest inhabitants of freshwater ecosystems that were still recovering from the Cretaceous-Paleogene extinction.